Cancer and non-cancer mortality among French uranium cycle workers: the TRACY cohort. Issue 4 (5th April 2016) - Samson, Eric; Piot, Irwin; Zhivin, Sergey; Richardson, David B; Laroche, Pierre; Serond, Ana-Paula; Laurier, Dominique; Laurent, Olivier
Abstract : Objectives: The health effects of internal contamination by radionuclides, and notably by uranium, are poorly characterised. New cohorts of uranium workers are needed to better examine these effects. This paper analyses for the first time the mortality profile of the French cohort of uranium cycle workers. It considers mortality from cancer and non-cancer causes. Methods: The cohort includes workers employed at least 6 months between 1958 and 2006 in French companies involved in the production of nuclear fuel. Vital status and causes of death were collected from French national registries. Workers were followed-up from 1 January 1968 to 31 December 2008. Standardised mortality ratios (SMRs) were computed based on mortality rates for the French general population. Results: The cohort includes 12 649 workers (88% men). The average length of follow-up is 27 years and the mean age at the end of the study is 60 years. Large mortality deficits are observed for non-cancer causes of death such as non-cancer respiratory diseases (SMR=0.51 (0.41 to 0.63)) and circulatory diseases (SMR=0.68 (0.62 to 0.74)). A mortality deficit of lower magnitude is also observed for all cancers combined (SMR (95% CI): 0.76 (0.71 to 0.81)). Pleural mesothelioma is elevated (SMR=2.04 (1.19 to 3.27)). Conclusions: A healthy worker effect is observed in this new cohort of workers involved in the uranium cycle. Collection of individual information on internal uranium exposure as well as other risk factors is underway, to allow for the investigation of uranium-related risks.